External Conditions and Debt Sustainability in Latin America - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2013)
Highly favorable external conditions have helped Latin America strengthen its economic fundamentals over the last decade. But, has the region built enough buffers to guard itself from a weakening of the external environment? This paper addresses this question by developing a simple framework that integrates econometric estimates of the effect of global factors on key domestic variables that determine public and external debt dynamics, with the IMF's standard debt sustainability framework. Results suggest that, while some countries in the region are well placed to withstand moderate or even large shocks, many would benefit from having stronger buffers to be in a position to deploy countercyclical policies, especially under tail events. External sustainability, on the other hand, does not appear to be a source of concern for most countries.